Imaging in Advanced Non–Small Cell Lung Cancer: A Medical Oncology Perspective. Issue 4 (July 2016) - Dimou, Anastasios; Sherman, Carol; Wrangle, John
Abstract : Treatment advances have improved outcomes in patients with lung cancer, with a number of targeted therapies and immunotherapies now approved for patients with metastatic disease. Along with longer survival, modern treatment paradigms have increased therapeutic decision-making complexity underscoring informative imaging as paramount in guiding clinical care. In this review, we summarize challenges the thoracic oncologist encounters in common clinical settings. In addition, we explore unmet needs for future investigations with particular focus on positron emission tomography technology and immunotherapies.